2021
DOI: 10.3390/nano11113125
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to Improvement of Fatigue Properties of Zr-4 Alloy: Gradient Nanostructured Surface Layer versus Compressive Residual Stress

Abstract: The gradient nanostructured (GNS) layer forms beneath the surface of Zr-4 samples by the surface mechanical grinding treatment (SMGT) process, which increases the fatigue strength apparently due to the synergistic effect of the gradient nanostructured layer and compressive residual stress. The SMGTed Zr-4 samples are subjected to annealing to remove residual stress (A-SMGT) and the individual effect of the GNS layer and compressive residual stress can be clarified. The results show that the gradient nanostruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…In the study performed by Han et al [24] regarding Zr, they found that the nanograined pure Zr was stable during annealing treatments performed at temperatures of up to 650 • C for 10 h, above which significant grain growth occurred. A similar conclusion for Zr-4 alloy was drawn by Geng et al [49]. Liu et al [22] investigated the thermal stability of pure Al by carrying out isothermal and isochronal annealing treatments.…”
Section: Heat Treatmentsupporting
confidence: 63%
See 1 more Smart Citation
“…In the study performed by Han et al [24] regarding Zr, they found that the nanograined pure Zr was stable during annealing treatments performed at temperatures of up to 650 • C for 10 h, above which significant grain growth occurred. A similar conclusion for Zr-4 alloy was drawn by Geng et al [49]. Liu et al [22] investigated the thermal stability of pure Al by carrying out isothermal and isochronal annealing treatments.…”
Section: Heat Treatmentsupporting
confidence: 63%
“…Since the nanocrystalline layer induced by surface treatment is generally associated with compressive residual stress and work hardening, post-treatment annealing has been applied as a method to relieve the residual stress after surface treatment, so that the individual influence of the nanostructure can be analyzed separately [49]. As illustrated in Figure 9a, once the residual stress is apparently relieved after annealing at 400 • C for 2 h, the annealed nanocrystallized Zr-4 samples exhibit a comparable fatigue striation space to the as-treated samples, and this striation space is significantly lower than that observed for the coarse-grain samples.…”
Section: Nanocrystalline Layermentioning
confidence: 99%
“…Post-treatment annealing can be applied to relieve residual stress in order to analyze the individual effect of the nanostructured layer. 41) However, it needs to pay attention to the stability of the nanostructured layer, while analyzing its effect on mechanical resistance especially under cyclic loading 233) or in an elevated temperature environment. Sun et al 77) investigated the potential changes of the microstructural characteristics generated by SMAT under subsequent LCF loading.…”
Section: Nanostructured Layermentioning
confidence: 99%
“…As for cyclic loading, recently Geng et al 41) studied the respective contributions of GNS region and CRS with a Zr-4 alloy processed by SMGT. Similarly, they performed annealing to remove residual stress in order to investigate the individual effects of GNS and residual stress.…”
Section: Residual Stress Versus Other Parametersmentioning
confidence: 99%